VALENŢE CONTEMPORANE ALE ORIENTĂRII DE MARKETING ÎN BIBLIOTECILE UNIVERSITARE DIN REPUBLICA MOLDOVA - KULIKOVSKI, Conferențiar universitar , Lidia (BIBLIOPOLIS, 2020)
The thesis Marketing orientation as a strategy for the development of university libraries in Moldova which is part of contemporary directions of library development. The author evaluates the work and highlights particular significance for higher education, the university library role in knowledge development, introduction of the library marketing problem as priority direction in the processus of improving the library management of today's conditions; emphasizes the relevance of the theme of the thesis, exemplifying each chapter of the book; the value of the work, the products. The recommendations will make efficient the National Library System.